ANTHROPOMETRIC PROFILE OF KOSOVO ELITE FEMALE VOLLEYBALL PLAYERS - SELIMI M.; GJINOVCI B.; MIFTARI F. (Editura Universitatii Transilvania din Brasov, 2019)
The purpose of this research is to confirm the anthropometric structure and profile of Kosovo elite female volleyball players. The sample for this study included 116 trained women volleyball players from nine clubs of Kosovo Volleyball Super League (19.91±3.59 years old). The results of this study demonstrate that Kosovo elite female volleyball players' mean body height is 172.21±6.14 cm, whereas their body mass index, determined by the weight-to-height ratio averages (BMI) 20.47 (kg/m2 ). The results of this research study, confirmed the average body height and body weight, measure the girth and skinfold, also determined the body mass index of Kosovo elite female volleyball players.